Assessing the educational impact and quality of medical microvideos on TikTok: the case of Latin America - Juan S. Izquierdo-Condoy; Marlon Arias-Intriago; Melizza Mosquera-Quiñónez; Fernando P. Melgar Muñoz; Mariana Jiménez-Ascanio; Valentina Loaiza-Guevara; Esteban Ortiz-Prado (Medical Education Online)
Background Social media use in medical education has surged, with YouTube and Facebook leading before COVID-19. Recently, TikTok has drawn young learners, expanding access but often lacking alignment with formal curricula and quality standards.Objectives This study aims to analyze the quality of academic medical content on TikTok within the Latin American context, focusing on the most-viewed Spanish-language accounts.Materials and methods This cross-sectional study analyzed medical education microvideos on TikTok through a systematic search conducted on 1 March 2024, using the keywords ‘medical education’ and ‘medical review.’ The search yielded 300 microvideos, from which the 100 most-viewed were selected. The 13 most popular accounts were identified, and their top three most-viewed microvideos were analyzed, resulting in a final sample of 39 microvideos. Popularity was measured through views, likes, and the Viewability Index (VPI), while educational quality was assessed using the JAMA Benchmark Criteria, which evaluates authorship, attribution, disclosure, and validity.Results The majority of accounts (69.2%) were male-created, with 30.8% based in Mexico and Peru. Physicians comprised 53.8% of content creators, followed by medical students (23.1%). General medical education was the main focus (69.2%), with general medicine as the most common topic (76.9%). The dataset included 39 microvideos, averaging 1,653,677 views, and #medicina was the most frequently used hashtag. Popularity metrics strongly correlated with engagement metrics (comments, shares) but weakly with favorites. Educational quality scores were low, with only two accounts scoring 1 out of 4 points on the JAMA Benchmark.Conclusion TikTok’s engagement metrics amplify popular medical microvideos among Spanish-speaking users but do not reliably reflect educational quality, raising concerns about misinformation. ‘Favorites’ may serve as a more accurate indicator of perceived informational value. Standardized assessment tools should incorporate both engagement and quality metrics to improve content reliability and accessibility to evidence-based medical information.